Public policy and the old age revolution in Japan - Bass, Scott A.; Morris, Robert, 1910-2005; Oka, Masato (Haworth Press, 1996)
"Public Policy and the Old Age Revolution in Japan captures the vitality of Japanese policymakers and the challenges they face in shaping a modern society responding to its changing needs. The rapid transition to an aging society poses a set of complex policy and resource dilemmas; the responses taken in Japan are of great value to policymakers, professionals, and students in the fields of gerontology, Asian and Japanese studies, sociology, public policy, administration and management, and anthropology in other industrial aging societies."--Jacket